2021
DOI: 10.1111/tid.13768
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and outcomes of BK viremia among deceased donor kidney transplant recipients based on donor characteristics

Abstract: Introduction: BK polyomavirus (BKV) is a common infection among kidney transplant recipients (KTR). Risk factors and outcomes based on donor characteristics remain largely unknown. Methods:In this study, we aimed to analyze the impact of donor factors through a paired kidney analysis. We included 289 pairs of adult deceased donor transplants (578 KTRs total); each pair had received kidneys from the same donor. Recipient pairs were divided into three groups: "no BK group" if neither KTR developed BK viremia (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…As previously described, 10 the majority of KTRs at our center receive induction immunosuppression with either a depleting agent (anti‐thymocyte globulin or alemtuzumab) or a non‐depleting agent (basiliximab), followed by a triple immunosuppressant regimen of tacrolimus, mycophenolic acid, and prednisone titrated to maximum tolerated doses. Recipients were started on tacrolimus as soon as possible at 8 am or 6 pm post‐transplant at the dose of .05 mg/kg to .1 mg/kg/day in two divided doses by mouth.…”
Section: Methodsmentioning
confidence: 99%
“…As previously described, 10 the majority of KTRs at our center receive induction immunosuppression with either a depleting agent (anti‐thymocyte globulin or alemtuzumab) or a non‐depleting agent (basiliximab), followed by a triple immunosuppressant regimen of tacrolimus, mycophenolic acid, and prednisone titrated to maximum tolerated doses. Recipients were started on tacrolimus as soon as possible at 8 am or 6 pm post‐transplant at the dose of .05 mg/kg to .1 mg/kg/day in two divided doses by mouth.…”
Section: Methodsmentioning
confidence: 99%
“…Previous single-center studies have identified the following possible risk factors for BKV reactivation: deceased donor transplantation, donor BK viruria, donor female sex, increased number of human leukocyte antigen (HLA) mismatches, recipient age (younger children and older adults), recipient male sex, increased immunosuppression, perioperative ureteric stents, and delayed graft function. 1,2,10,[12][13][14][15][16][17] The general sequence of BKV disease progression after kidney transplantation has been described in retrospective and prospective studies, with 30%-60% of recipients developing BK viruria, 10%-20% of these developing BK viremia, and 5%-10% of these developing BKVN, nearly always in that order. 2 Despite this predictable overall pattern identified in multiple cohort studies, there is a relative lack of prospective studies with sufficient frequency in monitoring to define the true natural history of BKV infection.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, most adult kidney donors could transmit latent BKV to organ recipients, where BKV reactivation (of either donor‐derived or native latent virus) can occur in the setting of post‐transplant immunosuppression. Previous single‐center studies have identified the following possible risk factors for BKV reactivation: deceased donor transplantation, donor BK viruria, donor female sex, increased number of human leukocyte antigen (HLA) mismatches, recipient age (younger children and older adults), recipient male sex, increased immunosuppression, perioperative ureteric stents, and delayed graft function 1,2,10,12–17 …”
Section: Introductionmentioning
confidence: 99%
“…However, there have been few case reports and series on BKPyV viruria and viremia among other solid organ transplant recipients, including the heart, lung, or liver, without significant detrimental kidney function in these patients ( 5 ). The existing body of research has compiled a comprehensive list of additional potential risk factors; however, the majority of these risk factors are either ambiguous, inconsistently identified across studies, or contradicted by findings from different studies: for example, tacrolimus-based immunosuppression regimens, deceased donor recipients, male recipients, acute rejection, and ureteral stent placement, donor–recipient human leukocyte antigen (HLA) mismatch >4, donor BKPyV seroreactivity, older recipient, previous transplant, steroid pulses, and many more ( 20 ). On the other hand, Drachenberg et al found an inverse relationship between the level of HLA matches and graft survival among recipients with BKPyVAN.…”
Section: Introductionmentioning
confidence: 99%
“…Further, evidence suggests BKPyV viremia is predominantly donor-derived rather than a reactivation of the recipient's latent infection ( 24 ). In one contemporary study among deceased donor kidney transplant recipients, where both kidneys were transplanted in the same single center, Breyer et al noticed a higher donor body mass index to be protective against BKPyV viremia, and having concordance or discordance of BKPyV viremia in the recipients receiving deceased donor kidneys from the same donor in two different recipients was not associated with inferior outcomes ( 20 ). Similarly, in another study, Srivastava et al noticed, pre-transplant hypoalbuminemia to be one of the risk factors for post-transplant BKPyV viremia ( 25 ).…”
Section: Introductionmentioning
confidence: 99%